Addressing women’s construction health and safety needs in Africa - Samuel H. P. Chikafalimani (AOSIS, 2021)
Concerns have been raised in Africa to address women’s construction health and safety needs adequately. These concerns include less participation of women in the sector, low income and less benefits being given to women, lack of adequate protective construction clothing suited for women, unfavourable employment conditions for women, and lack of construction site security and other facilities for women. This research article provides an overview of the suggested solutions to address the concerns raised. In addition, practical interventions being implemented by the Durban University of Technology and Makerere University research collaboration project team to address women’s needs in construction health and safety through women empowerment and involvement in construction research, education and practice in Africa are outlined. The main approaches applied in this research study are as follows: use of relevant publications on women’s construction health and safety needs in Africa and analysis of data obtained from reliable construction professional bodies in South Africa and Uganda to demonstrate gender imbalances.